EKSPANSI DAN MIGRASI Studi Kasus Negeri Besi Kabupaten Maluku Tengah Propinsi Maluku - Charles Y. Pesurnay (BALAI ARKEOLOGI PAPUA, 2010)
Seram island is the largest island in Mollucas propinves, which is a many differences tribe was live in it. Alune and Wemale is the biggest tribe in Seram island, also there’s other tribe beside it. The other tribe we can found it Seram island is from Bali, Buton, Bugis, Jawa, etc. Patasiwa and Patalima is a part of society group in Seram island are very famous, further this group Patasiwa and Patalima always fighting one to each other, just for depend there land. Patalima group is very polite, and very kind for anybody who come to island for living, especially for a guess, Patasiwa is opposite. Patasiwa territorial from south to west seram island, Patalima territorial from north to east seram island. For both group Patasiwa and Patalima always war, so many people they migration out of the siklus war for get a good living and future, from south to north. As well as Opin village and Besi village. The true is, this both village exactly in south seram.